LA TRONADORA EN LA DIABETES POR ALOXANA - MONTEMAYOR MARTINEZ, OFELIA (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1948)
51 cases of typhoid were treated as follows: 4 with polymyxin B, 34 with aureomycin and 13 with chloramphenicol The clinical diagnosis was established by demonstration of Salmonella typhosa bacteremia in 41 cases and by rise in antibody titer (Widal test
BOL INST ESTUD MED BIOL
Keywords: TRONADORA, DIABETES, ALOXANA; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA CLINICA